TRANSFORMASI KOMPETENSI PEDAGOGIK GURU MELALUI PROGRAM DUTA 8 PARU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN IPAS - Devi Wahyuningsih; Endah Andayani; Sulistyo; Ari Brihandhono (LPPM STAI Muhammadiyah Probolinggo, 2026)
The low quality of integrated science and social studies (IPAS) learning in elementary schools is a major challenge in the implementation of Kurikulum Merdeka. This study aims to analyze the effect of the Duta 8 Paru Program on the quality of IPAS learning, both directly and through teacher pedagogical competence as a mediating variable. This study employed a quantitative approach with an explanatory survey design. The population consisted of 46 teachers who implemented the program, and the entire population was selected as the sample using a saturated sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS 4 software. The results showed that the Duta 8 Paru Program had a significant direct effect on the quality of IPAS learning (β=0.422; p<0.05). Furthermore, teacher pedagogical competence acted as a significant partial mediator in this relationship (indirect effect=0.258; p<0.05). The structural model of the study had strong predictive ability, with an R² value of 0.611 for the quality of IPAS learning and a large predictive relevance (Q²=0.427). These findings conclude that the effectiveness of the Duta 8 Paru Program in improving the quality of IPAS learning will be very strong if accompanied by an increase in teacher pedagogical competence.